(untitled) (Research, Society and Development, 2023)
Introduction: Although lifestyle modifications are universally recognized as the first-line treatment for type 2 diabetes mellitus (T2DM), adequate glycemic control is difficult to achieve in most obese patients. Medications help control the symptoms of diabetes but cannot prevent disease progression. The aim of this study is to elucidate the role of restrictive diets in glycemic control and remission of type 2 diabetes. Methodology: This is an integrative review, in which the guiding question was "Does calorie restriction allow remission and improvement of glycemic control in patients with type 2 diabetes mellitus? The search for articles was performed in the main databases (PubMed, Scielo, and Google Scholar) using the terms "calorie restriction" and "type 2 diabetes" combined with Boolean operators. Results and discussion: There are several ways of nutritional intervention, with or without the addition of drugs, which may lead to improved glycemic control and even remission of T2DM. The superiority of carbohydrate restriction over calorie-restricted diets remains controversial, with studies showing benefits in both types of intervention. Intermittent periods of dieting have also been shown to be beneficial. Conclusion: Therefore, restrictive diets are effective in glycemic control and are able to lead to remission of type 2 diabetes mellitus in the medium to long term. Further studies should be done to clarify the best dietary change for this type of patient.